Model of Periodization of the History of Civilization and Phases of Development of Islamic Education - Nur Atika Alias (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This research aims to discuss the periodization model of the history of civilization and the development phases of Islamic education. The historical periodization of Islamic civilization and Islamic education developed simultaneously because education existed because of the existence of a civilization. Islamic civilization and education began with the presence of Islam in Mecca. The Prophet established that Islamic education is based on the Koran and Hadith so that all the values of Islamic education are found in the Koran. Harun Nasution divides the history of Islamic civilization into three periods, namely the classical period, the medieval period and the modern period. The development of Islamic education goes hand in hand with the historical development of Islamic civilization. In the classical period, Islamic education was centered on the Prophet, Khulfaur Rasyidin, the Umayyad daulah and the Abbasid daulah. In the middle period, Islamic education focused on three large empires, namely the Ottoman Empire in Turkey, the Safavid empire in Persia and the Mughal empire in India. Meanwhile, in the modern period Islamic education experienced significant changes because in the medieval period Islam experienced decline. Islamic education was born with a new face to develop Islamic education in various aspects.